\(\frac{x+3}{-4}=\frac{5}{20}\)

2.\(\frac...">

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 8 2015

a) \(\frac{x+3}{-4}=\frac{5}{20}\)

\(\frac{-\left(x+3\right)}{4}=\frac{1}{4}\)

- x - 3 = 1

- x = 1 + 3

- x = 4

x = - 4

b) \(\frac{2x+3}{7}=\frac{x-1}{15}\)

15.(2x + 3) = 7.(x - 1)

30x + 45 = 7x - 7

30x - 7x = - 7 - 45

23x = - 38

x = \(\frac{-38}{23}\)

18 tháng 7 2018

a,x-2/5=5/7

x=5/7+2/5

x=39/35

b,-2/5.x=4/15

x=4/15:-2/5

x=-2/3

18 tháng 7 2018

a) \(x-\frac{2}{5}=\frac{5}{7}\)

\(x=\frac{2}{5}+\frac{5}{7}\)

\(x=\frac{14}{35}+\frac{25}{35}=\frac{39}{35}\)

b)

\(\frac{-2}{5}x=\frac{4}{15}\)

\(x=\frac{4}{15}:-\frac{2}{5}\)

\(x=\frac{4}{15}\cdot-\frac{5}{2}=-\frac{2}{3}\)

c) \(2x\left(x-\frac{1}{7}\right)=2x^2-\frac{2x}{7}\)

d) \(\frac{1}{2}+\frac{3}{4}x=\frac{1}{4}\)

\(\frac{3}{4}x=\frac{1}{4}-\frac{1}{2}\)

\(\frac{3}{4}x=-\frac{1}{4}\)

\(x=-\frac{1}{4}\cdot\frac{4}{3}=-\frac{1}{3}\)

f) \(\frac{11}{12}-\left(\frac{2}{5}+x\right)=\frac{2}{5}\)

\(\frac{2}{5}+x=\frac{11}{12}-\frac{2}{5}=\frac{31}{60}\)

\(x=\frac{31}{60}-\frac{2}{5}=\frac{7}{60}\)

25 tháng 7 2017

\(=\frac{16}{5}.\frac{15}{16}-\left(\frac{3}{4}+\frac{2}{7}\right):\left(\frac{-29}{28}\right)\)

\(=3-\left(\frac{21}{28}+\frac{8}{28}\right):\left(\frac{-29}{28}\right)\)

\(=3-\left(\frac{29}{28}\right).\left(\frac{-28}{29}\right)\)

\(=3-\left(-1\right)\)

\(=4\)

b)   \(=\left(\frac{1}{4}+\frac{25}{2}-\frac{5}{16}\right):\left(12-\frac{7}{12}:\left(\frac{3}{8}-\frac{1}{12}\right)\right)\)

       \(=\left(\frac{4}{16}+\frac{200}{16}-\frac{5}{16}\right):\left(12-\frac{7}{12}:\left(\frac{3.3}{2.3.4}-\frac{2}{2.3.4}\right)\right)\)

     \(=\left(\frac{199}{16}\right):\left(12-\frac{7}{12}:\left(\frac{9}{24}-\frac{2}{24}\right)\right)\)

      \(=\frac{199}{16}:\left(12-\frac{7}{12}.\frac{24}{7}\right)\)

    \(=\frac{199}{16}:\left(12-2\right)\)

\(=\frac{199}{16}:10\)

\(=\frac{199}{160}\)

c)   \(\left(\frac{-3}{5}+\frac{5}{11}\right):\frac{-3}{7}+\left(\frac{-2}{5}+\frac{6}{5}\right):\frac{-3}{7}\)

\(\left(\frac{-33}{55}+\frac{25}{55}\right):\frac{-3}{7}+\left(\frac{4}{5}\right):\frac{-3}{7}\)

\(\left(\frac{-8}{55}\right).\frac{-7}{3}+\frac{4}{5}.\frac{-7}{3}\)

\(\frac{-7}{3}\left(\frac{-8}{55}+\frac{4}{5}\right)\)

\(\frac{-7}{3}.\frac{36}{55}=\frac{-84}{55}\)

     

25 tháng 7 2017

giờ mk phải đi ngủ r mai mk làm cho 

27 tháng 9 2019

a)\(\left(\frac{4}{5}\right)^{2x+7}=\left(\frac{4}{5}\right)^4\)

=> 2x + 7 = 4 

     2x        = 4 - 7 

     2x        = -3

       x        = -3 : 2

       x         = -1,5

   Vậy x = -1,5

19 tháng 9 2019

a) \(-\frac{3}{x}=\frac{15}{7}\)
=> -3.7 = 15x
=> 15x = -21
=>     x = -21:15
=>     x = -1,4
Vậy x = -1,4
b) \(\frac{x+3}{4}=\frac{5}{20}\)
\(\Rightarrow\frac{x+3}{4}=\frac{1}{4}\)
=> x + 3 = 1
=> x       = 1 - 3
=> x       = -2 
Vậy x = -2
d) \(\frac{x-1}{3}=\frac{x+1}{5}\)
=> 5(x - 1) = 3(x + 1)
=> 5x - 5   = 3x + 3
=> 5x - 3x = 5 + 3
=> 2x        = 8
=>   x        = 8:2
=>   x        = 4
Vậy x = 4

19 tháng 9 2019

\(a,\frac{-3}{x}=\frac{15}{7}\)

=> -21 = 15x

=> \(x=-\frac{21}{15}=-\frac{7}{5}\)

b, 

\(\frac{x+3}{4}=\frac{5}{20}\)

=> \(\frac{5(x+3)}{20}=\frac{5}{20}\)

=> 5\((x+3)\)= 5

=> x + 3 = 1

=> x = -2

\(c,\frac{1,2}{30}=\frac{3x+4}{50}\)

=> \(\frac{\frac{12}{10}}{30}=\frac{3x+4}{50}\)

=> \(\frac{\frac{6}{5}}{30}=\frac{3x+4}{50}\)

=> \(\frac{2}{50}=\frac{3x+4}{50}\)

=> 3x + 4 = 2

=> 3x = -2

=> x = -2/3

\(d,\frac{x-1}{3}=\frac{x+1}{5}\)

=> 5[x - 1] = 3[x + 1]

=> 5x - 5 = 3x + 3 

=> 5x - 5 - 3x = 3

=> 5x - 3x - 5 = 3

=> 2x = 8

=> x = 4

8 tháng 10 2019

a, \(-\frac{5}{7}-\left(\frac{1}{2}-x\right)=-\frac{11}{4}\)

\(\frac{1}{2}-x=\frac{57}{28}\)

\(x=-\frac{43}{28}\)

b, \(\left(2x-1\right)^2-5=20\)

\(\Rightarrow\left(2x-1\right)^2=25\)

\(\Rightarrow2x-1=\pm5\)

\(\Rightarrow\left[{}\begin{matrix}2x-1=5\\2x-1=-5\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}2x=6\\2x=-4\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}x=3\\x=-2\end{matrix}\right.\)